(untitled) (International Journal of Integrative Research (IJIR), 2024)
The perception of the electric two-wheelers (EVs) among Generation Z respondents in Ahmedabad, through the brands of TVS IQube and Ola, is studied using the quantitative approach that encompasses questions related to factors influencing familiarity, awareness, and attitudes toward EVs, among the younger consumer. Main key findings-age and familiarity were highly associated with each other in the case of EVs and more young consumers should be cited as liable for being open to new technologies. Close friends and family appear to have had the greatest impact on the perceptions on the side of social influence. Good environmental awareness was also found, as well as a positive attitude toward the eco-friendliness of EVs, although there was concern about unaffordability as a key blocking factor on the way toward adoption. Finance in general-including flexibility-end. The findings reveal that electric vehicles need effective targeted marketing strategies, charging infrastructure improvement, and coherent communication of environmental benefits in order to promote adoption among Generation Z. Finally, the study provides recommendations to the manufacturers, marketers, and policymakers regarding nurturing growth in the electric vehicle market in an urban context. Longitudinal studies, comparative analyses, and post-purchase behavior between EV users are proposed future research directions